Aktive Frequenzvervielfacher zur Signalerzeugung im Millimeter- und Submillimeterwellen Frequenzbereich - Lewark, Ulrich (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2015)
In this work a new transistor topology for frequency multiplication is developed, achieving relative bandwidths of complex and balanced structures with only four transistors. It enables the highest bandwidth in active multiplication beyond 110 GHz. Cascading techniques are shown enabling a cascaded frequency multiplier by eight with a frequency range of 220 to 320 GHz. For the first time an active frequency multiplier by six reaches output frequencies up to 670 GHz.